CLASS TEST PERFORMANCE CAN BE A PREDICTOR OF SCORES IN ANNUAL EXAM FOR A PRECLINICAL MEDICAL STUDENT - Naeem Yaqoob; Saeed Akram Bhatti et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT OBJECTIVE: To assess the usefulness of class tests by comparing their results with annual University examination results of preclinical medical students. STUDY DESIGN: A cross sectional analytical study METHODOLOGY: All (82) preclinical students of 2nd year MBBS passing the First Professional Part-II in first attempt were included in the study. Average of class test results of each student during the 2nd year was entered as percentage and compared with percentage total marks of same students in their 1st professional Part-II examination conducted by the University. Data maintained by Physiology Department was entered and analysed by SPSS 21. Descriptive statistics in the form of numbers and percentages were used and further analyzed using Pearson Correlation and Paired T Test of Significance. The p value of < 0.05 was considered to be significant. RESULTS: Out of total 82 students 65(79.3%) were females and 17(20.7%) males. All students were within the age group of 17-20 years, mean age being 18.7 years. Mean test score was 70.55 (Range=57-84, Median=71.19). Percentage marks in annual exam had a mean of 70.70 (Range=61-80, Median=71). Class test average in percentage was directly assessed against the percentage marks obtained in annual exam for each student. The average performance in class tests was significantly related to the marks in the final exam (p=0.01). Performance difference was noted amongst different genders in the class tests (Mean 65.27 for Males Vs 71.93 for Females) but not in the annual exam (Mean 69.75 for Males Vs 70.95 for Females) CONCLUSION: In preclinical years in a medical college regular class test results may be good predictors of the academic performance in professional examination. Male students show a tendency to improve their performance in the annual examination as compared to female students.